1998
DOI: 10.1111/j.1469-7793.1998.00963.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rapid eye movement (REM) sleep on upper airway mechanics in normal human subjects

Abstract: It has been proposed that the upper airway is more compliant during rapid eye movement (REM) sleep than during non‐rapid eye movement (NREM) sleep. The purpose of this study was to test this hypothesis in a group of subjects without sleep‐disordered breathing. On the first night, the effect of sleep stage on the relationship of retropalatal cross‐sectional area (CSA; visualized with a fibre‐optic scope) to pharyngeal pressure (PPH) measured at the soft palate during eupnoeic breathing was studied. Breaths duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
2
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 33 publications
2
47
2
1
Order By: Relevance
“…Our laboratory and others have utilized and validated FOB in multiple studies (Rowley et al, 1998; Rowley et al, 2002; Sankri-Tarbichi et al, 2009). To mitigate these limitations, we determined and fixed the locations of the scope and the catheter to the nasal mask after locating the retro palatal space.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our laboratory and others have utilized and validated FOB in multiple studies (Rowley et al, 1998; Rowley et al, 2002; Sankri-Tarbichi et al, 2009). To mitigate these limitations, we determined and fixed the locations of the scope and the catheter to the nasal mask after locating the retro palatal space.…”
Section: Discussionmentioning
confidence: 99%
“…The absolute value of retro palatal CSA was obtained from five different phases of the respiratory cycle (B I : beginning inspiration, P I : peak inspiration, E I /B E : end inspiration and beginning expiration, P E : peak expiration, E E : end expiration) by manually outlining the retro palatal lumen using computer software (Sigma Scan, Jandel) in mm 2 (Figure 2). The ability to reproduce this technique has been previously validated by our laboratory (Morrell et al, 1998a; Morrell et al, 1998b; Rowley et al, 1998; Rowley et al, 2002). For each image, the scanning software provided an area in pixels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also showed that the sleep-related narrowing was greater in patients with obstructive sleep apnoea compared with healthy subjects and in obese relative to thin patients . During REM sleep, the pattern of airway narrowing is similar, although the magnitude of the changes were smaller than those that occurred during non-REM sleep (Rowley et al 1998).…”
Section: The Effects Of Sleep On Pharyngeal Patency In Humansmentioning
confidence: 74%
“…We also showed that the sleep-related narrowing was greater in patients with obstructive sleep apnoea compared with healthy subjects and in obese relative to thin patients . During REM sleep, the pattern of airway narrowing is similar, although the magnitude of the changes were smaller 68 than those that occurred during non-REM sleep (Rowley et al 1998).Pharyngeal transmural pressure can also be affected by sleep-related changes in extraluminal pressure. In normal subjects and in patients with obstructive sleep apnoea, our group have found that complete pharyngeal occlusion occurred during spontaneous and induced central sleep apnoeas (Badr et al 1995), i.e.…”
mentioning
confidence: 73%